Nutrition Education and Nutritional Status of Chronic Lack of Energy Pregnant Women in PUSKESMAS Work Areas Throughout Kupang City - Agustina Setia; Asmulyati S Saleh; Tobianus Hasan; Maria F Vinsensia D P Kewa Niron; Agustina W. Djuma (Postgraduate, University of Mataram, 2024)
One of the indirect causes of preventable maternal and child mortality is the health status of pregnant women. Pregnant women with SEZ conditions are at risk of experiencing decreased muscle strength, which is needed in the process of labor so that it can result in fetal death, premature birth, birth defects, low birth weight babies, short birth babies and even infant death. The design used is quantitative with a cross sectional approach with univariate and bivariate analysis using the Chi-Square test. The population of this study were all pregnant women who did pregnancy checks at the Puskesmas in Kupang City in 2022. Sample technique using purposive sampling technique. This study was conducted from January to December 2022. The results showed that of all pregnant women who were given nutrition education in the form of counseling and provision of additional food, most experienced weight gain. In contrast to the increase in LiLA, although there is a change in the size of LiLA after being given education, there are still pregnant women who do not experience changes in LiLA. The statistical test results obtained a p-value <0.005, which means that there is a relationship between the provision of nutrition education and the improvement of the nutritional status of pregnant women with SEZ. It is expected for health workers to carry out special monitoring of pregnant women at risk of SEZ in conducting health checks and consuming additional nutritionally balanced foods.